Population’s preference of rhinoceros beetle (Oryctes rhinoceros) between oil palm (Elaeis guineensis) and coconut palm (Cocos nucifera l.): Contributing to pest’s controlling strategy - Ismail, Izaitul Aida; Zaini, Mohd Rasdi; Mazran, Noor Shuhaina Shaikh; Hasin, Ahmad Khairuman Mohd (Asian Journal of Agriculture and Rural Development, 2023)
The rhinoceros beetle (Oryctes rhinoceros) began to establish itself in Malaysia with the emergence of coconut cultivation. Rhinoceros beetles were well adapted to survive on oil palm (Elaeis guineensis) and coconut (Cocos nucifera L.) trees. Different host plants could have different interactions and food preferences with the Rhinoceros beetle against their host plant, even within the same family. Additionally, climatic change, particularly rainfall, could also influence the population dynamics of O. rhinoceros especially in terms of the biological aspect of the pest. This study was carried out to evaluate the difference in population of rhinoceros beetles between oil palm and coconut palm as a preference host comparison in relation to the climatic factors on the plantation scale. The population of rhinoceros beetles was found to be higher in oil palm as compared to coconut palm. It can be concluded that rhinoceros beetles highly prefer oil palms when compared to coconut palms. This study highlighted the importance of planting similar families in order to reduce the risk of pest attacks. This study also found that climate is one of the factors influences the population dynamics of rhinoceros beetles and puts pressure on plants, subsequently making it a favorable condition for rhinoceros beetles in the field. Interestingly, female rhinoceros beetle in an oil palm field was significantly correlated with the rainfall. Therefore, preventive measures need to be taken during the rainy season, considering the high risk of planting nearby and/or similar plants.